Creative Economy and Culture Challenges, Changes and Futures for the Creative Industries - Hartley, John; Wen, W.; Li, Henry (SAGE, 2015)
Instead of confining cultural expression to talented artists and expert professionals, this book investigates creative new ideas from everyone.